Aufarbeitungsprojekte der Außenstelle Sana’a, Jemen - Gerlach, Iris (e-Forschungsberichte des DAI, 2023)
Tan’im is regarded as the most important urban centre in the Khawlan, a closed mountainous region east of Sana’a, the capital of Yemen. The Khawlan covers a surface area of more than 2500 km2 with mountains reaching a height of over 3000 m and with a transforming area between the mountains and the desert. Tan’im is the single urban complex in the Khawlan that was founded in the 1st millennium BC. The branch office of the DAI in Sana’a is studying continuity and disruption in the city’s history, particularly during the transition from the Bronze Age to the Iron Age.